Effectiveness Of Pjbl-Based Steam Learning Model On Students' Creativity Mis Al Islam Bengkulu - Della; Sofi Anjelita; Andre Taulani Sandi Andariwanii; Dalima Septiria (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aims to determine the effectiveness of the STEAM (Science, Technology, Engineering, Art, and Mathematics) learning model based on Project-Based Learning (PjBL) on the creativity of fifth-grade students at MIS Al Islam Bengkulu. The study was motivated by the students' low level of creativity during the learning process, characterized by a lack of confidence in expressing ideas, low participation, and limited opportunities for creative expression. A quantitative approach was employed using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of two classes totaling 50 students: Class V-A served as the experimental group receiving STEAM-PjBL instruction, while Class V-B served as the control group receiving conventional instruction. Data collection techniques included tests (pre-test and post-test), observation, and documentation. Data analysis involved normality tests, homogeneity tests, independent t-tests, and N-Gain calculations. The results showed that the experimental group achieved an average post-test creativity score of 83.4, compared to 70.6 for the control group; the significance value of p = 0.001 (<0.05) indicated a significant difference. N-Gain analysis revealed a creativity improvement of 0.60 in the experimental group (moderate-to-high category), whereas the control group showed an improvement of 0.23 (low-to-moderate category). Observations also indicated high levels of student engagement in discussions, project design, and the presentation of results. Thus, it can be concluded that the STEAM learning model based on Project-Based Learning (PjBL) is effective in enhancing student creativity at MIS Al Islam Bengkulu.